Buckling Analysis and Section Optimum for Square Thin-Wall CFST Columns Sealed by Self-Tapping Screws. (15th January 2019) - Zhang, He; Wu, Kai; Xu, Chao; Ren, Lijian; Chen, Feng
Abstract : Two columns of thin-walled concrete-filled steel tubes (CFSTs), in which tube seams are connected by self-tapping screws, are axial compression tested and FEM simulated; the influence of local buckling on the column compression bearing capacity is discussed. Failure modes of square thin-wall CFST columns are, first, steel tube plate buckling and then the collapse of steel and concrete in some corner edge areas. Interaction between concrete and steel makes the column continue to withstand higher forces after buckling appears. A large deflection analysis for tube elastic buckling reflects that equivalent uniform stress of the steel plate in the buckling area can reach yield stress and that steel can supply enough designing stress. Aiming at failure modes of square thin-walled CFST columns, a B-type section is proposed as an improvement scheme. Comparing the analysis results, the B-type section can address both the problems of corner collapse and steel plate buckling. This new type section can better make full use of the stress of the concrete material and the steel material; this type section can also increase the compression bearing capacity of the column.